Patient satisfaction with health status in rheumatoid arthritis based on remote assessment: a pilot OPTIMA study (Patient-reported Outcomes, Severity and Medical care in Arthritis) - E. Yu. Polishchuk; A. E. Karateev; H. R. Makhmudov; K. S. Kalashnikov; N. A. Bulgakova; A. M. Lila (Современная ревматология)
Leading Russian and international experts recognize the necessity of incorporating patient-reported outcomes (PROs) into the dynamic monitoring of rheumatoid arthritis (RA) patients. An integral indicator of general well-being and treatment satisfaction is the Patient Acceptable Symptom State (PASS).Objective: To assess patient satisfaction with their health status and treatment outcomes in RA and to evaluate its relationship with key disease manifestations through remote PROs assessment.Material and methods. From January 2023 to November 2024, an online survey was conducted involving 2,115 RA patients (88.3% women, mean age 46.4±13.9 years, median disease duration 6 [3; 13] years). The survey assessed demographics, therapy, PASS, and PROs (pain, fatigue, anxiety, depression, daily activity limitations, patient global assessment [PGA], using a numerical rating scale [NRS], 0–10). Among respondents, 80% were receiving conventional synthetic disease-modifing antirheumatic drugs (DMARDs), 23.8% biologic DMARDs (bDMARDs) or Janus kinase inhibitors (JAKi). Glucocorticoids (GCs) were used by 39.7%, and nonsteroidal anti-inflammatory drugs (NSAIDs ) by 67.9% of patients.Results and discussion. A positive assessment of their health status (PASS+) was reported by 45.8% of patients. Mean NRS scores were: pain – 5.6±2.7, fatigue – 6.2±2.7, PGA – 5.5±2.5, median anxiety – 5 [3; 8], depression – 5 [2; 7], daily activity limitations – 5 [3; 7]. Dissatisfaction (PASS-) was associated with male gender, moderate (≥4) or high (≥7) NRS PRO scores, and the use of GCs and NSAIDs. bDMARD and JAKi therapy showed an inverse association with PASS-. A binary logistic regression model was developed to predict PASS- in RA patients with an accuracy of up to 71%. ROC curve analysis revealed a threshold value of the logistic function P at 49.6%, area under the curve (AUC) – 0.740 (95% CI 0.718–0.762), model sensitivity – 82%, specificity – 60%.Conclusion. Fewer than half of RA patients were satisfied with their health status when assessed remotely. PASS is closely associated with PROs and may serve as an integral indicator of health status and treatment satisfaction in RA.